Pelatihan Kiat Menjadi Pelaku UMKM yang Lebih Maju - Kaleb, Setiawirawan Valerian; Praditya, A.G. Arvin; Rahman, M. Ardafi Sulchia; Setyaji, Ghalih Anung; Aditia, Amar; Widatama, Krisna; Kuswanto, Jeki; Pramitasari, Rina (Institut Teknologi Pendidikan Indonesia, 2024)
Today internet can now be used as a marketing or digital marketing medium for product promotion. By using the internet, we can expand our target market net, and the use of the internet can be used for digital marketing which promotes and markets products via the internet to reach potential consumers in a fast process. The hope to be achieved is for business actors to become more optimal and get maximum results by utilizing digital marketing. BEE1 Culinary is located in the culinary area at Cempaka Culinary Center, Jl. Sawo Kecik, Gempol, Condongcatur, District. Depok, Sleman Regency, Special Region of Yogyakarta, has started his business for 2 years. This business currently still uses the traditional method, namely by just waiting for people to buy the business's products on the spot. A problem has arisen, namely the lack of people joining the BEE1 culinary project, the main aim of which is to help lower income people to sell with additional capital from the franchise owner, and the profits obtained will be distributed evenly to other branches as well. The output of this activity is the availability of an information system to help promote products in the form of social media such as Facebook and Instagram so that it is hoped that it can increase the number of consumers and have a wider reach and increase orders.